Macrophages and Metabolic Reprograming in the Tumor Microenvironment - Liu, Jin; Gao, Mingwei; Yang, Zhou; Zhao, Yidan; Guo, Kun; Sun, Binwen; Gao, Zhenming; Wang, Liming (Frontiers in Oncology, 2022)
Due to the emergence of traditional drug resistance in tumor treatment, the anti-cancer therapies are facing multiple challenges. Immunotherapy, as a new and universal treatment, has been gradually concerned. The macrophages, as an important part of the immune system, play an important role in it. Many studies have shown that immune state is essential in cancer progression and prognosis, rebuilding the architecture and functional orientation of the tumor region. Most tumors are complex ecosystems that change temporally and spatially under the pressure of proliferation, apoptosis, and extension of every cell in the microenvironment. Cancer always manifests in the form of trophic, metabolic, immunological, and therapeutic components. The scientists have gradually found that the macrophages play different functions in different metabolic states. We first briefly introduce the two states of macrophages activation. Then we discuss the cytokines secreted by macrophages in different metabolic states playing the different immunological functions and we also focus on the formation of immune exhaustion. Finally, we look forward to the explorations of clinical treatment for immune metabolism process.